Direct shear performance of UHPC Multi-Keyed epoxy joint. (October 2022) - Pan, Rensheng; Cheng, Lingxiao; He, Weiwei; Zhou, Xuan; Shen, Xiujiang
Abstract: The modular Ultra-High Performance Concrete (UHPC) girder elements show outstanding potential to produce lightweight superstructure with high quality, low lifecycle cost and excellent durability for precast segmental bridge; and the required connection between segments is critically important to ensure desirable overall structural performance. This paper presents the results of direct shear tests on 18 UHPC joint specimens considering the influence of the number of shear keys, confining stress, depth of shear key, steel fiber volume content of UHPC and joint type. The shear behavior was characterized in terms of load-slip response, shear resistance, cracking pattern, and failure mode. Two types of failure modes, namely synchronous and stepwise shear failure, were observed. These specimens with stepwise shear failure showed smaller shear resistance and higher ductility compared with those with synchronous shear failure. And the ultimate shear stress decreased with the increase of key number, while the positive effect from confining stress was identified for the shear resistance in general. In addition, an updated model based on the existing ones was proposed and validated against the test data (standard deviation of 0.11).